ANALISIS KEBUTUHAN AIR BERSIH PADA INSTALASI PENGOLAHAN AIR BERSIH KECAMATAN SANGA SANGA KABUPATEN KUTAI KARTANEGARA - TAHSURUR, AHMAD (KURVA S JURNAL MAHASISWA, 2018)
Clean water is a very important part of all the basic needs of living things, especially for humans. Humans use water for various purposes in their daily lives. This research was conducted at the Clean Water Treatment Plant of PDAM Tirta Mahakam, Sanga-Sanga Branch, Kutai Kartanegara Regency, East Kalimantan Province, aimed at analyzing the need for clean water for population growth in 2018 to 2028. From the data obtained from PDAM Tirta Mahakam the discharge capacity of clean water produced is 40 liters / second, with the longest distant distribution network at 13,000 meters leading to the village, the type of pipe used is HDPE pipe with a diameter of 203 , 2 mm, with a roughness level of 130. The results of the calculation and analysis of clean water needs in Sanga-Sanga Subdistrict, noramal water needs in 2028 (10-year projection) of 38,703 liters / second and the peak water demand in 2028 (peak discharge) of 67,731 liters / second. From the results of the hydraulic analysis the main distribution pipeline network towards the neighborhood is very much needed, the flow velocity in the pipe is 1.052 meters / second with a pressure loss of 76.2 meters, so that the distribution of clean water needs of the community can be maximized.